Simulation of Electromagnetic Waves Propagation Using Matlab - S., Praveena; J., Deepak; K., Priyadharshini; T., Shanthi (Journal of Electronics and Informatics, 2024)
This research explores the simulation of electromagnetic wave propagation using MATLAB, focusing on both 2D and 3D environments. By deriving the wave equation from Maxwell's equations, we utilize the Finite Difference Time Domain (FDTD) method for numerical solutions. The MATLAB code implementation demonstrates the propagation of electric and magnetic fields and is validated through visualizations. Practical applications, including telecommunications, medical imaging, and microwave engineering, are examined through case studies on antenna design and waveguide analysis. Challenges in simulation, recent advances, and future research directions are discussed, providing a comprehensive overview of electromagnetic wave propagation and its technological implications.
Keywords: Electromagnetic Wave; Maxwell's equation; Finite Difference Time Domain; Telecommunications; Medical Imaging; Microwave Engineering